2001
DOI: 10.1562/0031-8655(2001)073<0642:cpitpt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Phenomena in Two-pulse, Two-color Laser Photocoagulation of Cutaneous Blood Vessels¶

Abstract: A novel laser system has been developed to study the effects of multiple laser pulses of differing wavelengths on cutaneous blood vessels in vivo, using the hamster dorsal skin flap preparation and in vitro, using cuvettes of whole or diluted blood. The system permits sequenced irradiation with well-defined intrapulse spacing at 532 nm, using a long-pulse frequency-doubled Nd:YAG laser, and at 1064 nm, using a long-pulse Nd:YAG laser. Using this system, we have identified a parameter space where two pulses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The absorption coeff icient of whole blood (.100 cm 21 at the 532-nm wavelength) is much larger than the averaged absorption coefficient of the gray and white matter of the brain (ϳ0.56 cm 21 at 532-nm wavelength). 15,16 Therefore, the contrast of the PAT images presented here actually reveals the blood hemoglobin concentrations in various brain tissues.…”
Section: Drivermentioning
confidence: 85%
“…The absorption coeff icient of whole blood (.100 cm 21 at the 532-nm wavelength) is much larger than the averaged absorption coefficient of the gray and white matter of the brain (ϳ0.56 cm 21 at 532-nm wavelength). 15,16 Therefore, the contrast of the PAT images presented here actually reveals the blood hemoglobin concentrations in various brain tissues.…”
Section: Drivermentioning
confidence: 85%
“…Although more commonly used to treat unwanted lower extremity vessels, these wavelengths may offer new options for treating selected PWSs. In addition, investigators have shown that coupling of 532 and 1,064 nm lasers during the same pulse may show even greater promise than using a single wavelength alone [27,28]. An experimental laser utilizing this one-two punch, termed the ''Buster Douglas'' after the famous boxer by the same name, utilizes a two-wavelength approach to exploit changes that take place in the intravascular hemoglobin during the delivery of the laser pulse.…”
Section: Discussionmentioning
confidence: 99%
“…5A, upper curve) because of metHb formation. Percent changes of m a (l) listed in Table 5 present trends rather than actual changes since during pulsed laser heating nonlinear effects will occur [17][18][19][20][21][22][23][24][25][26]. Using the Hb conversion dynamics and Equations 1A, 2A (see Appendix), we have calculated radiant exposures E(l,D) required for heating blood-filled capillaries.…”
Section: Modelingmentioning
confidence: 99%
“…Several photothermal in vitro [16][17][18][19] and in vivo [8,9,11,[20][21][22][23][24][25][26] studies have observed that during heating, blood undergoes transient or irreversible biophysical events that may have a significant impact on treatment outcome [16][17][18][19][20][21][22][23][24][25][26]. During slow heating, red blood cells (RBCs) change shape from discs to spheres, followed by membrane denaturation, formation of holes, and egress of hemoglobins (Hb), all of which change the scattering properties of blood [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation